Little Buddha - Thomas, Jeremy; Bertolucci, Bernardo ([S.l.] : Bernardo Bertolucci [production company] ; Kuala Lumpur : Berjaya HVN Sdn. Bhd. [distributor])
Lama Norbu comes to Seattle in search of the reincarnation of his dead teacher, Lama Dorje. His search leads him to young Jesse Conrad, Raju, a boy from Kathmandu, and a Indian girl. Together, they journey to Bhutan where the three children must undergo a test to prove which is true reincarnation. Interested with this, is the story of Siddharta, later known as the Buddha
n.2 is acquisition for KPI (Kelab Pencinta Ilmu)
Story, Bernardo Bertolucci ; screenplay, Rudy Wurlitzer, Mark Peploe
Cast: Keanu Reeves, Chris Isaak, Bridget Fonda
Keywords: Feature films; Monks -- Tibet -- Drama; Buddhism -- Drama